Second generation of didactical Engineering: Development of an ethnogeometric teaching resource based on the Kalinga tribe's material culture - Hortelano, Julius Ceasar (Animo Repository, 2021)
Kalinga’s batek (traditional tattoo) and laga (textiles), as part of the material cultures of the province, are ‘geometric’ in nature aside from naturally implied as cultural. Through the second generation of Didactical Engineering (DE), this study presents the development of an Ethnogeometric Teaching Resource (ETR) for the primary teachers that is beneficial for Teaching Strategy (TS) and Geometric Content Knowledge (GCK). The content were emphasized on undefined terms, symmetry, and tessellation based on DepEd’s MELCs and K to 12 mathematics curriculum. Nine (9) primary teachers and two (2) teacher-trainers participated in the study. Preliminary analysis included the MATHTED and DOST-SEI’s principle on realistic mathematics, the ethnomathematical approach, first interview, and pre-test. These preliminary findings were the basis of the design and a priori assumptions which were organized into TS, GCK, and appropriateness. Realization tested these assumptions by administering the ETR, second interview, Communication Index (.008), and post-test. A posteriori analysis and validation showed that teacher participants’ exposure with the ETR provided potential TS, developed GCK, and appropriate to their level. Besides a teaching resource, this can also be a reference in designing self-made and contextualized modules as a contribution to Kalinga’s culture propagation. Keywords: Didactical Engineering, Ethnogeometry, Cultural Education, Teaching Resource, Material Development